Pengaruh Model Pembelajaran Problem Based Learning Terhadap Kemampuan Literasi Numerasi - Zamaiyah, Zamaiyah; Maysarah, Siti; Ammamiarihta, Ammamiarihta (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2026)
This study aims to determine whether or not there is an influence of the problem-based learning model on the numeracy ability of class VIII students of SMP Islam Setia Nurul Azmi on the material of relations and functions in the 2025/2026 academic year. This study is motivated by the low numeracy ability of students, which is caused by the use of conventional learning models that are less effective, so that innovative learning strategies are needed according to student needs. This study uses a quantitative approach using a quasi-experimental method. The research design used is a pre-test post-test control group design. The subjects in this study were students of class VIII-E as an experimental class with a total of 30 students and class VIII-B with a total of 30 students as a control class. The data collection technique used a numeracy ability test given before and after treatment. Then the data obtained were analyzed using a t-test. The results showed that there was an influence of the problem-based learning model obtained from the t_count value of 1.850 and the t_table value of 1.672. By comparing the calculated t_value with the t_table, which is 1.850>1.672. Thus, H_O is rejected and H_a is accepted, which means there is an influence of the problem-based learning model on students’ numeracy literacy abilities.